Penggunaan Teknologi Artificial Intelligence dalam Kinerja Praktisi Public Relations - Riwanda, Josephine Kayla; Yoetadi, Moehammad Gafar (Prologia, 2025)
Artificial Intelligence (AI) is increasingly adopted by Public Relations (PR) practitioners to enhance performance. AI technologies, such as ChatGPT (OpenAI), are utilized in various aspects, including data analysis, personalization, and automation of routine tasks. This study aims to examine the impact of Artificial Intelligence (AI) utilization on the performance of Public Relations (PR) practitioners. The respondents for this research consist of 100 PR practitioners from diverse backgrounds, including state-owned enterprises, private companies, and Public Relations (PR) agencies. The research employs a quantitative approach using purposive sampling techniques, with questionnaires as the primary data collection tool. The findings reveal a significant positive influence of Artificial Intelligence (AI) adoption on the performance of Public Relations (PR) practitioners. The correlation coefficient test yields a value of 0.745, indicating a very strong relationship between the two variables. Additionally, the determination test shows a value of 55.5%, suggesting that Artificial Intelligence (AI) technology significantly impacts Public Relations (PR) performance. This demonstrates that the use of Artificial Intelligence (AI) improves work quality optimization, resource utilization, proficiency, accuracy, and overall work outcomes for Public Relations (PR) practitioners. Therefore, this study recommends a broader adoption of Artificial Intelligence (AI) technology to support the professionalism of Public Relations (PR) practitioners. Artificial Intelligence (AI) saat ini semakin banyak diadopsi oleh praktisi Public Relations (PR) untuk meningkatkan kinerja. Teknologi Artificial Intelligence (AI) seperti ChatGPT (OpenAI) digunakan dalam berbagai aspek, seperti analisis data, personalisasi, dan otomatisasi tugas rutin. Penelitian ini bertujuan untuk mengkaji pengaruh penggunaan Artificial Intelligence (AI) terhadap kinerja praktisi Public Relations (PR). Responden penelitian ini adalah 100 praktisi Public Relations (PR) dengan latar belakang yang beragam, meliputi perusahaan BUMN, swasta, dan agensi Public Relations (PR). Penelitian ini menggunakan pendekatan kuantitatif dengan teknik purposive sampling dan instrumen kuesioner sebagai alat pengumpulan data. Hasil penelitian menunjukkan adanya pengaruh positif signifikan antara penggunaan Artificial Intelligence (AI) dan kinerja praktisi Public Relations (PR). Uji koefisien korelasi menghasilkan nilai 0,745, yang menunjukkan hubungan yang sangat kuat antara kedua variabel. Selain itu, uji determinasi menunjukkan angka 55,5% yang menunjukan adanya pengaruh teknologi Artificial Intelligence (AI) terhadap kinerja Public Relations (PR). Hal ini membuktikan bahwa penggunaan Artificial Intelligence (AI) mampu meningkatkan pengoptimalan kualitas kerja, pemanfaatan sumber daya, kecakapan dan ketelitian, serta capaian hasil kerja praktisi Public Relations (PR). Oleh karena itu, penelitian ini merekomendasikan adopsi teknologi Artificial Intelligence (AI) secara lebih luas untuk mendukung profesionalisme praktisi Public Relations (PR).